Evaluasi Peningkatan Kapasitas Perangkat Desa dalam Penggunaan Aplikasi - Yudi Arsa; Isnan Hari Mardika; Gusneli Gusneli (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
this study aims to evaluate the impact of capacity building for village officials in Anjir Seberang Pasar I Village on the effectiveness of village administrative and financial management following the implementation of Law No. 6 of 2014. The primary focus of the study is to measure changes in the competencies of village officials before and after the implementation of technical guidance, as well as the use of the Village Financial System (Siskeudes) application and Internet Banking Business. The research method used is qualitative with a case study approach, in which data collection was conducted through observation, interviews, and the completion of pre-test and post-test questionnaires by respondents consisting of the Village Secretary, Kaur, and Kasi. The results of the study indicate a significant increase in three key variables: perceived usefulness, perceived ease of use, and attitude toward using. Quantitatively, the average validation score from respondents reached 4.53 (on a 5.0 scale), which falls into the “Agree” category regarding the system’s effectiveness. Based on data analysis, the success rate of capacity building for village officials was recorded at 29.23%, with a final understanding rate reaching 91.33%. These findings indicate that practice-oriented and participatory training is capable of improving the technical skills and accountability of village officials in managing digital-based government administration. The integration of Siskeudes and digital banking has proven to have a positive impact on a safer and more transparent payroll system at the village level.